Management of Critically Ill Children with Acute Necrotizing Encephalitis during an H1N1 Outbreak in a Tertiary Pediatric Hospital: A Series of Three Cases and Literature Review - D'Eleuterio, Annalisa; Rufini, Paolo; L'Erario, Manuela; Simonini, Gabriele; Montagnani, Carlotta; Ermini, Stefano; Ricci, Silvia; Bartolini, Luca; Ricci, Zaccaria (Neuropediatrics, 2024)
Acute necrotizing encephalopathy (ANE) is a severe neurological condition that is diagnosed clinically and upon specific radiological imaging. Medical treatment of this condition is uncertain, and timing is likely very important to minimize brain damage and systemic inflammation. The present case series describes three patients suffering from ANE secondary to influenza A/H1N1 infection during a recent outbreak, treated with increasingly aggressive anti-inflammatory approach, and with significantly different outcomes.
Keywords: acute necrotizing encephalopathy; critically ill children; immunomodulation; influenza A